Ocular comorbidities and its relation to clinical and dermoscopic features in patients with alopecia areata: a case-control study - Eman R. M. Hofny; Ahmed F. Omar; Walaa M. Abdel Megeed; Ayman M. Mahran (Journal of the Egyptian Women’s Dermatologic Society)
Background Alopecia Areata (AA) is considered a systemic autoimmune disease that can be associated with several comorbidities. Several ocular alterations have been previously reported in patients with AA. Previous studies about ocular findings in AA are controversial. Objective To study the ocular comorbidities in patients with AA and evaluate dermoscopic features of AA in relation to such comorbidities. Patients and methods 65 patients with the clinical diagnosis of AA and 33 age and sex-matched volunteers were included in this case control study. Each patient was subjected to history taking, clinical examination, dermoscopic evaluation, and ophthalmological examination. Results Ocular findings were significantly higher in AA patients (90.8%) versus controls (60.6%). Errors of refraction were the commonest ocular findings in AA patients (89.2%). Other ocular findings (anterior segment changes, increased IOP, fundus changes, madarosis) could be detected in a respectable percentage of AA patients. The commonest dermoscopic findings in patients were broken hair (55.4%), vellus hair (52.3%) and black dots (40%). Broken hair and black dots were significantly higher in patchy multiple AA. However, vellus hair was significantly higher in patchy localized AA. No significant relation between ocular and dermoscopic findings could be detected. Conclusion Ocular comorbidities, especially errors of refraction are common in AA patients. Dermoscopic findings are not predictive of such comorbidities.